2022
DOI: 10.1063/5.0097866
|View full text |Cite
|
Sign up to set email alerts
|

Atomic resolution analysis of extended defects and Mg agglomeration in Mg-ion-implanted GaN and their impacts on acceptor formation

Abstract: We carried out atomic-scale observations of Mg-ion-implanted GaN by transmission electron microscopy (TEM) and atom probe tomography (APT) to clarify the crystallographic structures of extended defects and Mg agglomerations that form during post-implantation annealing. The complementary TEM and APT analyses have shown that Mg atoms agglomerate at dislocations that bound extended defects. The concentration of Mg is higher at the dislocations with a larger Burgers vector. This indicates that Mg agglomeration is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…The present work showed that the vacancy-type defects introduced by ion implantation exist even after UHPA at 1480°C, and they are expected to play a critical role in the formation of secondary defects and their atomic configuration. 20,33 Thus, knowledge on defect reactions revealed by the combination of characterization techniques used in the present work will shed light on finding appropriate annealing parameters for the fabrication of p-type GaN by Mg-implantation.…”
Section: Resultsmentioning
confidence: 95%
“…The present work showed that the vacancy-type defects introduced by ion implantation exist even after UHPA at 1480°C, and they are expected to play a critical role in the formation of secondary defects and their atomic configuration. 20,33 Thus, knowledge on defect reactions revealed by the combination of characterization techniques used in the present work will shed light on finding appropriate annealing parameters for the fabrication of p-type GaN by Mg-implantation.…”
Section: Resultsmentioning
confidence: 95%
“…Figure n shows such an IDB, where the 1 4 or 3 4 <0001> translation results from a mirror plane inserted along the hexagonal (0001) basal plane. Heavily Mg-doped , or Mg ion-implanted , GaN have been shown to form this defect type due to Mg incorporation at an apex, eventually developing into a translated inverted pyramid. The dotlike defect described by Iwata et al in Mg ion-implanted GaN, which has a similar 1 4 <0001> translation, may also take the form of this defect.…”
Section: Atomic Structure Of Defectsmentioning
confidence: 99%
“…This is considered to be due to the partial extension of dislocations in the loop. [55] Figure 12a shows the distribution of Mg atoms in the sample with sequential N-implantation. The Mg clusters indicated by letters (b, c, d, and e) appeared as planar shapes along with the c-plane.…”
Section: Impact Of N-implantation On Mg Activation and Secondary Defe...mentioning
confidence: 99%